Job demands, resources, and task performance in Chinese social workers: Roles of burnout and work engagement - Tu, Bin; Luo, Xiaoting; Sitar, Sophie; Huang, Chienchung (Frontiers in Public Health, 2022)
Social work is a rapidly developing occupation in China. In the early 2000s, there were merely a few hundred thousand social workers, but by 2018 there are over 1.2 million social workers in the field. However, research has indicated these social workers are also experiencing record high burnout and turnover rates. Thus, researchers have started to question the work engagement and task performance factors that could be contributing to these increasing rates. This study uses the Job Demands and Resources (JD-R) Theory to understand how 537 social workers from Guangzhou, China are impacted by burnout and how it influences work engagement and task performance. The results show JD-R directly affects task performance through burnout and work engagement via a dual process. First, job demands were correlated with high burnout and low work engagement, which both were found to lead to low task performance. Second, job resources were correlated with low burnout rates and high work engagement, both of which were associated with high task performance. These findings call for interventions to reduce burnout and promote work engagement to support task performance in social workers in China.